Hardness of Pillared-Graphene Nanostructures via Indentation Simulation. (20th December 2016) - Sasaki, R.; Shintani, K.
ABSTRACT: Pillared-graphene is one of nanocarbon hybrids. It consists of graphene sheets and carbon nanotubes (CNTs); the latter are bonded vertically to the former. In order to investigate the hardness of pillared-graphene, indentation simulations are performed using a molecular dynamics method. It is revealed that the hardness of pillared-graphene increases with increasing the diameter of the CNTs, whereas it decreases with increasing the distance between CNTs or temperature. Such tendencies can be understood by considering the deformations of graphene and CNTs individually.